The relation between fractional statistics and finite bosonic systems in one-dimensional case - Rovenchak, Andrij (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The equivalence is established between the one-dimensional (1D) Bose-system with a finite number ofparticles and the system obeying the fractional (intermediate) Gentile statistics, in which the maximum occupation of single-particle energy levels is limited. The system of 1D harmonic oscillators is considered providing the model of harmonically trapped Bose-gas. The results are generalized for the system with powerenergy spectrum.